Psychometric validation of a patient-reported outcome questionnaire (Qualipsosex) assessing the impact of psoriasis and psoriatic arthritis on patient perception of sexuality. Issue 1 (8th January 2021) - Lespessailles, Eric; Mahé, Emmanuel; Reguiai, Ziad; Begon, Edouard; Maccari, François; Beneton, Nathalie; Chaby, Guillaume; Rosenberg, Carole; Dernis, Emmanuelle; Roux, Fabienne; Henry-Desailly, Isabelle; Charles, Bénédicte; et al.
Abstract : Abstract: Psoriasis (Pso) and psoriatic arthritis (PsA) frequently have a negative impact on patients' sexual health. We have developed a specific questionnaire assessing the impact of Pso and PsA on patient perception of sexuality: the QualipsoSex Questionnaire (QSQ). The aim of the present study was to further validate this questionnaire by checking its psychometric properties including validity, reliability, and responsiveness. A cross sectional observational study with a longitudinal component for responsiveness and test–retest reliability was performed in 12 centers in France including 7 dermatologists and 5 rheumatologists. Psychometric properties were examined according to the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) check-list. At baseline, 114 patients had Pso and 35 patients had PsA including 17 peripheral arthritis, 4 axial disease, 13 patients with both axial disease and peripheral arthritis and one patient with an undifferentiated phenotype. The mean Pso Area and Severity Index score was 12.5. Genital organs were involved in 44.7% of Pso cases. Internal consistency, construct validity, and reliability were good with Cronbach's α coefficient, measure of sampling adequacy and intraclass correlation coefficient respectively at 0.87, 0.84, and 0.93. The QSQ also demonstrated acceptable sensitivity to change. The QSQ has demonstrated good psychometric properties fulfilling the validation process relative to the recommendations of the COSMIN check list. The QSQ is simple to score and may hopefully be valuable in clinical practice and in clinical trials. Abstract : Supplemental Digital Content is available in the text